LARGE BOWEL MICROBIOCENTOSIS IN IMMATURE INFANTS WITH VERY LOW AND EXTREMELY LOW BODY WEIGHT IN THE FIRST YEAR OF LIFE - O. G. Malygina; T. A. Bazhukova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
Aim. To assess qualitative and quantitative composition of culture large bowel bugs in immature infants with birth weight 1500 g and less during the first year of life. Materials and methods. Fecal matter culturing has been done in 58 immature infants with body weight 1500 g and less, who were under supervision during the year. Results. A significant deficit of large bowel micro-biocentosis in immature infants has been registered in the neonatal period. Up to 2 months of life a slow formation of bowel's microflora is observed mainly due to bifidus bacteria. Up to 1 year of life a formed colonic microbiota in immature infants was not observed firstly due to lactobacilli deficit and late formation of typical Escherichia. Conclusion. The process of large bowel microbiocentosis in immature infants with very low and extremely low birth weight is slowed down due to extended admission in the intensive care unit, absence of breast feeding and antybiotherapy.